Pengaruh terapi perilaku kognitif terhadap tingkat kemampuan interaksi sosial di ruang rawat inap rumah sakit jiwa - La Ode Alifariki; Adius Kusnan (Sekolah Tinggi Ilmu Kesehatan Harapan Ibu Jambi, 2019)
Backgound: Nursing education at the Southeast Sulawesi Provincial General Hospital has carried out effective learning in carrying out social interactions that are still not maximized by still comparing errors that occur and thoughts cannot be used with others. tools performed. The purpose of the study was to determine the citizenship conducted on the level of ability to interact in the inpatient ward of the Southeast Sulawesi Provincial Hospital in 2017. Method: This type of research is an experiment with a non-equivalent control group design. The study population was all social isolation patients in the inpatient ward of the Southeast Sulawesi Provincial Hospital in 2017 as many as 115 people. Examples of perfect research are 16 people. Statistical test which is a t test. Result: The results of the study before the interaction of patients who did not have the ability to do social as many as 16 people (100%) and after the deadlock to measure the ability of social communication as many as 11 people (68.8%) and at least the ability level of social interaction is not as much as 5 people ( 31.5%). There are those who use communication skills for the level of ability to interact in the inpatient ward of the Southeast Sulawesi Provincial Hospital (p = 0,000). Conclution:United Hospital wants to always apply general therapy with the implementation of strategies and group behavior on clients who can help patients in conducting social interactions.